2017
DOI: 10.4103/0973-1075.197958
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of povidone-iodine pleurodesis in malignant pleural effusions

Abstract: Introduction:Malignant pleural effusion (MPE) is determined by the detection of malignant cells in pleural fluid or pleural tissue. Neoplasm of lung, breast, ovary and lymphoma are the causes of more than 75% of MPE. Pleurodesis is a usual technique in the management of MPE to achieve a symphysis between two layers of the pleura, and various chemical agents have been used in an attempt to produce pleurodesis. With regard to complications and limitations of these sclerosing agents, efficacy and safety of povido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
11
1
3
Order By: Relevance
“…and also in a study by Olivares et al . [ 2 , 8 , 31 ]. These patients had analgesia with xylocaine during the procedure, the post procedure pain was mild and required only mild analgesia (paracetamol).…”
Section: Discussionmentioning
confidence: 99%
“…and also in a study by Olivares et al . [ 2 , 8 , 31 ]. These patients had analgesia with xylocaine during the procedure, the post procedure pain was mild and required only mild analgesia (paracetamol).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited literature on the efficiency of VATS iodopovidone-iodine pleurodesis for MPEs. 5 - 11 A 2016 Cochrane review consisting of 62 randomized trials including a total of 3 428 patients taken to pleurodesis yielded no studies involving a VATS iodopovidone-iodine pleurodesis approach for MPEs. 13 Agarwal et al reported a meta-analysis evaluating N=157 patients with pleural effusions treated with iodopovidone pleurodesis; N=144 through chest tubes and N=121 through thoracoscopy (for pneumothorax).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 90% of MPEs reoccur requiring repeated drainage, at this point permanent catheters may be placed, or pleurodesis considered if there is adequate lung expansion. 2 - 5 Contraindications for video-assisted thoracoscopic surgery (VATS) chemical pleurodesis include patient refusal, non-expanding lung, suspicion of current infection, concomitant adhesions requiring decortication, and less than one month of life expectancy. 2 , 3 Successful pleurodesis is defined as no re-accumulation for up to 30 days.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations